PENGARUH PERTUMBUHAN PERUSAHAAN, MATURITAS, DAN ARUS KAS OPERASI TERHADAP PERINGKAT OBLIGASI DI BURSA EFEK INDONESIA - admin, Rosita Naomi Sianturi B1021131112 (Jurnal Manajemen Update, 2017)
This study aims to provide empirical evidence about the effects of the corporate growth, maturity, and operating cash flows on the bond rating. This study was conducted on 34 bonds issued by the 16 non-financial companies on the Indonesia Stock Exchange which also issued bonds and are registered in the Indonesia Bond Market Directory and rated by PEFINDO during 2012 - 2014. The hypotheses in this study were tested using the logistic regression analysis. The results of this study show that the variable of corporateÂ  growth had a negative and significant effect on the bond rating. While maturity and operating cash flow had no significant effect on the bond rating. In addition, the firm size had a positive and significant effect on the bond rating. Keywords: corporate growth, maturity, operating cash flow, firm size, bond rating Â